(untitled) (Scientific journal of the Fergana State University, 2023)
In this work, the main structural components for creating a methodology for using digital technologies in secondary schools are shown, in which the system of principles of teaching using digital technology, the connection of the principles of using digital technology with the principles of classical and informational didactics.